Pengaruh Harga Dan Suasana Cafe Terhadap Kepuasan Pelanggan Dengan Minat Berkunjung Sebagai Variabel Intervening: Studi Kasus Pada Success Coffee Gayo KotaTebing Tinggi - Arfah, Yenni; Nursaimatussaddiya, Nursaimatussaddiya; Ananda, Ananda (Sekolah Tinggi Ilmu Ekonomi Bina karya, 2023)
This study aims to determine the effect of price and cafe atmosphere on customer satisfaction with interest in visiting as an intervening variable (Case Study on Success Coffee Gayo, Tebing Tinggi City). The research method used is a quantitative method using the help of SPSS version 25.00. Collected from the results of distributing questionnaires to customers of Success Coffee Gayo, Tebing Tinggi city, there were 96 respondents. The analytical method used in this study is using instrument tests, namely validity and reliability tests. The classic assumption test is the normality test, multicolonearity test, heteroscedasticity test, multiple linear regression analysis, analysis of the coefficient of determination (R2), hypothesis testing, namely the t test and path analysis (Path analysis). The results of the SPSS in this study are that the Price variable (X1) has an effect on the Interest in Visiting variable (Z), the Cafe Atmosphere variable (X2) has an effect on the Interest in Visiting variable (Z), the Price variable (X1) has no effect on Customer satisfaction (Y), Cafe Atmosphere (X2) has an effect on Customer Satisfaction variable (Y), Price variable (X1) has an effect on Customer Satisfaction variable (Y) through Interest in Visiting (Z), and Cafe Atmosphere variable (X2) has no effect on Customer Satisfaction variable (Y) through Interest in Visiting (Z).